1984
DOI: 10.1128/jcm.20.4.791-796.1984
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agent susceptibility patterns of bacteria in hospitals from 1971 to 1982

Abstract: Bacterial susceptibility to 16 commonly used antibiotics was analyzed for a 12-year period (from 1971 to 1982, inclusive). Susceptibilities of 5,828,243 strains isolated from a mean of 242 hospitals nationwide and of 194,575 strains isolated at the Massachusetts General Hospital, Boston, Mass., and the Bronx Lebanon Hospital Center, New York, N.Y., were compared. Strains of Escherichia coli, Staphylococcus aureus, Haemophilus influenzae, and Pseudomonas aeruginosa showed virtually the same susceptibilities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…However, no established procedure exists to control the interlaboratory variation in the way suggested by the work of KRONVALL O'Brien et al and therefore global surveillance on a larger scale using routine laboratory disc test results had to await a stricter standardization or the calibration of test results. Another early surveillance study using routine disc test results was a 12-year study including almost 10 million isolates from 242 hospitals in the United States (47).…”
Section: Global Resistance Surveillancementioning
confidence: 99%
“…However, no established procedure exists to control the interlaboratory variation in the way suggested by the work of KRONVALL O'Brien et al and therefore global surveillance on a larger scale using routine laboratory disc test results had to await a stricter standardization or the calibration of test results. Another early surveillance study using routine disc test results was a 12-year study including almost 10 million isolates from 242 hospitals in the United States (47).…”
Section: Global Resistance Surveillancementioning
confidence: 99%
“…Even though during the time effective medicines have emerged, at the same time some of them such as antibiotics have lost their activity due to the development of different mechanisms of antibacterial resistance, most importantly because of their misuse. Therefore, new medicines are always essential solutions to counteract this issue [19,20] .…”
Section: Short Communicationsmentioning
confidence: 99%
“…The first demonstration of transferable resistance among enterococci was made by Raycroft and Zimmerman, who showed that chloramphenicol resistance could be transferred from one strain of E. faecalis to another (171). Several studies have reported that 20 to 42% of enterococci are chloramphenicol resistant (1,6,22,209). When studied, this resistance has been mediated by chloramphenicol acetyltransferase (22).…”
Section: Acquired Resistancementioning
confidence: 99%
“…Erythromycin resistance plasmids and transposons are also commonly found in enterococci. Although strains from the Solomon Islanders studied by Moellering were all susceptible, strains with high-level erythromycin resistance have shown a steady increase in many locations (6,139). Erythromycin resistance occurs as part of the macrolide-lincosamide-streptogramin B resistance phenotype; in addition to erythromycin resistance, this determinant also confers HLR to clindamycin (22).…”
Section: Acquired Resistancementioning
confidence: 99%